Motor Overflow and Spasticity in Chronic Stroke Share a Common Pathophysiological Process: Analysis of Within-Limb and Between-Limb EMG-EMG Coherence - Chen, Yen-Ting; Li, Shengai; Magat, Elaine; Zhou, Ping; Li, Sheng (Frontiers in Neurology, 2018)
The phenomenon of exaggerated motor overflow is well documented in stroke survivors with spasticity. However, the mechanism underlying the abnormal motor overflow remains unclear. In this study, we aimed to investigate the possible mechanisms behind abnormal motor overflow and its possible relations with post-stroke spasticity. 11 stroke patients (63.6 yrs ± 6.4 yrs; 4 women) and 11 healthy subjects (31.18 yrs ± 6.18 yrs; 2 women) were recruited. All of them were asked to perform unilateral isometric elbow flexion at submaximal levels (10%, 30%, and 60% of maximum voluntary contraction). Electromyogram (EMG) was measured from the contracting biceps (iBiceps) muscle and resting contralateral biceps (cBiceps), ipsilateral flexor digitorum superficialis (iFDS), and contralateral FDS (cFDS) muscles. Motor overflow was quantified as the normalized EMG of the resting muscles. The severity of stroke was quantified through reflex torque (spasticity) and weakness. To investigate the possible cortical and subcortical origins of the abnormal motor overflow, EMG-EMG coherence was calculated between the contracting muscle and each of the resting muscles. During elbow flexion on the impaired side, stroke subjects exhibited significant higher motor overflow to the iFDS muscle compared with healthy subjects (ipsilateral motor overflow). Stroke subjects exhibited significantly higher motor overflow to the contralateral spastic muscles (cBiceps and cFDS) during elbow flexion on the non-impaired side (contralateral motor overflow), compared with healthy subjects. Moreover, there was significantly high EMG-EMG coherence in the alpha band (6-12Hz) between the contracting muscle and all other resting muscles during elbow flexion on the non-impaired side. Our results of diffuse ipsilateral and contralateral motor overflow with EMG-EMG coherence in the alpha band suggest subcortical origins of motor overflow. Furthermore, correlation between contralateral motor overflow to contralateral spastic elbow and finger flexors and their spasticity was consistently at moderate to high levels. Post-stroke spasticity is attributed to reticulospinal hyperexcitability secondary to the unmasking of ponto-medullary reticular formation. A high correlation between spasticity and motor overflow supports a potential role of reticulospinal activation in motor overflow. Collectively, these results suggest that diffuse motor overflow to the impaired side is likely related to activation of hyperexcitable reticulospinal pathways after stroke.